Does trading volume drive systemic banks' stock return volatility? Lessons from the Greek banking system - Athanasios Tsagkanos; Konstantinos Gkillas Gillas; Christoforos Konstantatos; Christos Floros (International Journal of Financial Studies, 2021)
The present research investigates the impact of trading volume on stock return volatility using data from the Greek banking system. For our analysis, the empirical study uses daily measures of volatility constructed from intraday data for the period 5 January 2001-30 December 2020. This period includes several market phases, such as the latest financial crisis, the European sovereign debt crisis and enforcement of restrictions on transactions owing to capital controls on the Athens Stock Exchange in June 2015. Based on the estimated quantile regressions, we find evidence of a direct impact of the trading volume on stock return volatility mainly in all quantiles. The findings extrapolated are of relevance and interest to financial (banking) analysts, policy makers and practitioners concerned with intraday data and volatility modeling.
Keywords: F65; G11; G12; G24; 330; extreme value theory; banks; Greece; intraday data; realized measures; volatility; volume